EXAMINING STUDENTS’ NEEDS FOR ENGLISH AS REQUIRED COURSE IN DIPONEGORO UNIVERSITY - Wulandari, Dwi (Master Program in Linguistics, Diponegoro University, 2015)
This study is aimed at finding out what students need in taking English as required course, what students want to learn, and how they want to learn. The data were taken from 500 questionnaires distributed to students. The data revealed that most of the students do have positive attitude in learning English, and because of this the students have more chances to take the best of their learning. However, as most of the students also take English because they are required to do so, there are also some factors that may discourage learners’ motivation in learning, i.e. materials selection, and teaching methods. Kajian ini ditujukan untuk mengetahui apa yang diinginkan oleh mahasiswa dalam mengambil mata kuliah MKDU Bahasa Inggris, secara spesifik untuk mengetahui materi apa yang mereka ingin pelajari, dan bagaimana mereka ingin mempelajarinya. Data diambil dari kuesioner yang disebarkan pada 500 mahasiswa. Analisis data menunjukkan bahwa sebagian besar siswa memiliki sikap bahasa yang positif dalam mepelajari Bahasa Inggris, dan oleh karenanya mahasiswa memiliki kesempatan lebih banyak untuk mengambil keuntungan terbesar dari perkuliahan tersebut. Namun demikian, karena sebagian besar mahasiswa mengambil mata kuliah tersebut karena kewajiban, ada beberapa hal yang menyurutkan motivasi mahasiswa, yakni pemilihan materi, dan metode mengajar dosen Bahasa Inggris.